Computational fluid dynamics modeling of flammable refrigerant leaks inside machine rooms: Evaluation of ventilation mitigation requirements. (18th May 2016) - Papas, Paul; Zhang, Shiling; Jiang, Hai; Verma, Parmesh; Rydkin, Ivan; Lord, Richard; Burns, Larry
Abstract : Computational fluid dynamics simulations were undertaken to quantify ventilation dilution requirements needed for mitigating flammability risks during leaks of flammable refrigerants from large chillers inside machine rooms. Machine rooms ranging in size from 376 to 2256 m 3 were modeled using computational fluid dynamics to simulate major leaks from a 2640 kW (750TR) chiller. As is required by existing safety standards, a refrigerant sensor was incorporated to trigger and activate an alarm or emergency level ventilation system to dilute the room with fresh air. A range of refrigerant leak rates and different alarm-triggered ventilation rates were evaluated to understand dilution requirements to prevent significant flammable mass accumulation. To verify the computational fluid dynamics findings, verification testing was also conducted in a 574 m 3 machine room setup using carbon dioxide as a surrogate refrigerant. When matching volumetric leak rates, computational fluid dynamics results were comparable with verification testing data. These results will be discussed in light of current machine room ventilation standards and used to establish a relationship for the alarm ventilation rate needed for mitigating risks for major refrigerant leaks inside machine rooms.